Actual analysis of complications after unicompartmental arthroplasty of the knee joint - Zhuk, P.M.; Movchaniuk , V.O.; Matsipura , M.M. (TERRA ORTHOPAEDICA, 2020)
Summary. In this literature review, a systematic analysis of modern data on the study of complications of unicompartmental arthroplasty of the knee, their prevalence, the main methods of treatment and prevention. Instability of the components of the endoprosthesis, wear of the polyethylene and progression of the degenerative process in the contralateral joint were found to have the highest frequency in the structure of complications. Additional factors for the development of negative effects of unicompartimental arthroplasty of the knee are local osteoporosis of the femur and tibia, periprosthetic fractures, infectious complications and pain syndrome.